Siglec‐7 specifically recognizes Campylobacter jejuni strains associated with oculomotor weakness in Guillain–Barré syndrome and Miller Fisher syndrome. (23rd November 2012) - Heikema, A. P.; Jacobs, B. C.; Horst‐Kreft, D.; Huizinga, R.; Kuijf, M. L.; Endtz, H. P.; Samsom, J. N.; van, W. J. B.; Cutler, S.
Abstract Due to molecular mimicry, Campylobacter jejuni lipo‐oligosaccharides can induce a cross‐reactive antibody response to nerve gangliosides, which leads to Guillain–Barré syndrome (GBS). Cross‐reactive antibodies to ganglioside GQ1b are strongly associated with oculomotor weakness in GBS and its variant, Miller Fisher syndrome (MFS). Antigen recognition is a crucial first step in the induction of a cross‐reactive antibody response, and it has been shown that GQ1b‐like epitopes expressed on the surface of C. jejuni are recognized by sialic acid‐binding immunoglobulin‐like lectin‐7 (Siglec‐7). We aimed to determine the epitope specificity of C. jejuni binding to Siglec‐7, and correlate the outcome to disease symptoms in GBS and MFS patients. Using a well‐defined GBS/MFS‐associated C. jejuni strain collection, which included three sialic acid knockout strains, we found that Siglec‐7 exclusively binds to C. jejuni strains that express terminal disialylated ganglioside mimics. When serological and diagnostic patient records were correlated with the Siglec‐7‐binding properties, we observed an association between Siglec‐7 binding and the presence of anti‐GQ1b antibodies in patient serum. In addition, Siglec‐7 binding was associated with oculomotor weakness in GBS and MFS patients. Lipo‐oligosaccharide‐specific binding of C. jejuni to Siglec‐7 may be an initiating event in immune recognition and presentation, and lead to anti‐GQ1b antibody production and the development of ocular weakness in GBS or MFS.